The Application of Think-Pair-Share and Reciprocal Teaching Strategy on Improving Students’ Reading Comprehension - Alviani, Fani; Khusaini, Khusaini; Christine, Linda (Foremost Journal, 2025)
This research aimed to finding out the effect of Think-Pair-Share and Reciprocal strategies and then the result both of those strategies above will be compared at the tenth grade students of SMK PGRI 31 Legok. This research is quantitative research with the quasi experimental research. The population of the research is the tenth grade students with the total population is 355. The researcher using the purposive technique sampling to choose the sample and got 108 students for three classes and consist 36 students each class. There are three classes those are X MP 1 as the class experiment which is taught by Think-Pair-Share, X MP as the experiment class which taught by Reciprocal Teaching Strategy, and X MP 3 as the controlled class which taught by Conventional Teaching Strategy. The result showed the students’ score of reading comprehension after being taught by those strategies are good because the mean of the total score of students’ Posttest which taught by using Think-Pair-Share is (68.94), and Reciprocal Teaching Strategy is (71.81). The mean of students’ posttest score on reading Comprehension which taught by Reciprocal teaching Strategy is bigger that the students which taught by Reciprocal Teaching Strategy. So, Reciprocal Teaching Strategy is effective that Think-Pair-Share on improving students’ Reading Comprehension.